Disguisable and Obvious Child Sexual Abuse Behaviors: Analysis of Effects on Sexual Addiction in Adults and Between-Sex Comparisons of Occurrence Percentages Using Anonymous Data From Perpetrators and Victims. Issue 3 (2nd October 2019) - Steele, Kerri; Stroebel, Sandra S.; O'Keefe, Stephen L.; Griffee, Karen; Harper-Dorton, Karen V.; Beard, Keith W.; Young, Debra H.; Swindell, Sam; Stroupe, Walter E.; Kuo, Shih-Ya; Hershman, Cassandra M.
Abstract: Anonymous retrospective data were input by 2, 828 female and 1, 556 male adult study participants using a study-specific computer program. Although adult males were more likely than adult females to select underage females for victims, adult females were more likely than adult males to select underage males for victims of both disguisable and obvious child sexual abuse in both data from perpetrators and data from victims. Logistic regression analysis of potential statistical predictors from early behaviors for being sexually addicted revealed that many were statistically significant in both females and males. The three most powerful predictors were identified in each sex.